Epidemiological pattern of corneal foreign bodies and awareness of patients on the utilization of protective eye devices- A hospital- based prospective study. - Sharma, Samata (2021)
EXECUTIVE SUMMARY: Ocular injuries are a major cause of preventable blindness worldwide and work-related eye injuries constitute a major public health problem. Among ocular occupational injuries, a corneal foreign body is the most common. Corneal foreign body occurs across a number of occupations like metallic workers, construction workers, electricians, carpenters etc. It is responsible for significant morbidity and economic burden due to significant amount of time taken off work. It can have significant consequence if left untreated leading to infective keratitis, conjunctivitis and even endophthalmitis. It can also cause scars on visual axis thereby permanently decreasing vision. Majority of eye injuries are preventable with health education and use of protective devices. In developing countries like Nepal, due to rapid urbanization and low level of literacy incidence of such injuries is high. This prospective cross-sectional study was conducted from April 2021 to August 2021 in the Hospital for Children, Eye, ENT, and Rehabilitation Services (CHEERS), Bhaktapur to evaluate the magnitude of such occupational injuries and care practices following the injury. Total 142 patients were included in the study among which 99.3% were male with mean age of the participants being 31.15 (±9.78) years. Most of the participants (85.9%) were migrant workers and more than two-third worked in the metallic and grill industry. The time lag between injury and presenting for consultation was 44.52 (±46.97) hour. A quarter of the study participants had already developed complications at the time of presentation. The average working day lost due to the foreign body was 1.16 (±1.16). 45.1% of the study participants physically tried to remove the foreign body either by self or with someone else's help and the most used material was handkerchief and other clothes (64.0%). More than half (52.1%) of study participants sought treatment at a local pharmacy, clinic, eye clinic or other hospitals without specialty eye services before consulting at an eye hospital and almost 60% were using some topical ocular medications. 31.7% were not aware of the need for protective eye wear at their workplace. Among aware of the need for protective eye wear 84.4% used either simple glasses or goggles while special protective eye wear or metallic shields were used by few. Corneal foreign body occurs predominantly in the young males working in metallic and construction industries. It results in absence from work leading to economic loss. Lack of awareness and non-compliance to protective eye wear is the main cause of such injuries. Regular and comprehensive educational workshops or awareness programs should be organized for the workers and their employers to minimize such injuries.